Multimodal representation of specialized knowledge in ontology-based terminological databases: the case of EcoLexicon - Clara Inés López Rodríguez; Juan Antonio Prieto Velasco; Maribel Tercedor Sánchez (JoSTrans: The Journal of Specialised Translation)
Multimodality is the construction of meaning through multiple modes of communication suited to the needs of different users. In this article we discuss the issue of multimodality in EcoLexicon, a multimodal Terminological Knowledge Base on the environment, and focus on the role of images in the representation of specialised knowledge (entities, events, properties and relations). Finally, we propose a series of principles that should guide the selection of multimodal resources with a view to their inclusion in terminological entries, and in order to highlight the ontological structure of EcoLexicon.